Soft tissue metric parameters, methods and aesthetic indices in implant dentistry: A critical review. (12th October 2021) - Cosyn, Jan; Wessels, Retief; Garcia Cabeza, Ricardo; Ackerman, Julie; Eeckhout, Célien; Christiaens, Véronique
Abstract: Objectives: The primary objective was to provide an overview of soft tissue metric parameters, methods, and aesthetic indices in implant dentistry. The secondary objective was to describe reliability and validity of aesthetic indices. Materials and methods: Two independent reviewers conducted an electronic literature search in Pubmed, Web of Science, Embase, and Cochrane databases up to October 2020 to identify studies on soft tissue metric parameters, methods, and aesthetic indices. Aesthetic indices were evaluated in terms of reliability and validity. Data extraction was performed by the same reviewers. Results: Five metric parameters (papilla height, linear changes in soft tissue level, color assessment, soft tissue thickness, and profilometric soft tissue changes) registered by means of several methods (intra‐oral registrations, radiographic assessments, digital analyses, and ultrasonic assessments), and 15 aesthetic indices (Papilla Index (PI), ad hoc questions scored with Visual Analogue Scales, Pink Esthetic Score (PES), Implant Crown Aesthetic Index (ICAI), Implant Aesthetic Score (IAS), Rompen Index, Subjective Esthetic Score, White Esthetic Score, Copenhagen Index, Complex Esthetic Index, Californian Dental Association Index (CDAI), Peri‐Implant, and Crown Index, Functional Implant Prosthodontic Score, Implant Restoration Esthetic Index (IREI), and Mucosal Scarring Index (MSI)) could be identified. With respect to metric parameters and methods, intra‐oral registrations were least accurate whereas profilometric soft tissue changes on the basis of digital surface models were most accurate. Six aesthetic indices showed good inter‐rater reliability (PI, PES, ICAI, CDAI, IREI, and MSI). Good validity could only be shown for two indices (PES and CEI). Given this and on the basis of ease of use and ease of interpretation, PES qualified best for clinical research on single implants. None of the indices fulfilled the quality criteria for clinical research on multiple implants. Conclusion: Many soft tissue assessment methods with varying reliability and validity have been described and used, which hampers uniform reporting in implant dentistry. Clinical investigators are advised to measure linear and profilometric soft tissue changes using digital surface models, and to use a reliable and validated aesthetic index. Currently, PES qualifies best for aesthetic evaluation of single implants. An index is to be developed to assess the aesthetic outcome of rehabilitations on multiple implants.